Media and Union Communication and Promoting Union Action in Algeria: A Socio-Media Approach - hammadi , hadjira (Journal of Social Sciences and Humanities, 2025)
This study analyses and interprets the nature of the relationship between the media, trade union communication and trade union action in Algeria, and the contexts of its transformations, based on a sociological analysis of trade union practices، and descriptive methodology, based on a purposive sample of data, announcements and electronic publications issued by three unions active in the health, higher education and national education sectors between 2022 and 2025, using indirect observation to examine how unions use media and communication in their activities. One of the main findings of the study is that the restriction of union, political, and media freedoms contributes to the weakness of both internal and external union media and communication, as well as union action, due to the lack of sufficient freedom to criticize economic and social policies that harm the working class. Due to the absence of discussion around the real issues that concern labor forces.